2013
DOI: 10.3390/nu5104231
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Human Growth, and the Global Epidemic of Obesity

Abstract: Iron is an essential nutrient utilized in almost every aspect of cell function and its availability has previously limited life. Those same properties which allow iron to function as a catalyst in the reactions of life also present a threat via generation of oxygen-based free radicals. Accordingly; life exists at the interface of iron-deficiency and iron-sufficiency. We propose that: (1) human life is no longer positioned at the limits of iron availability following several decades of fortification and supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 138 publications
(155 reference statements)
0
9
0
1
Order By: Relevance
“…Iron is an essential trace element utilized in almost every aspect of normal cell function and body growth [1]. Most iron is stored in ferritin, which is a ubiquitously expressed cytosolic iron-storage protein that forms a hetero-oligomeric protein shell composed of ferritin heavy chain (FTH) and ferritin light chain (FTL) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Iron is an essential trace element utilized in almost every aspect of normal cell function and body growth [1]. Most iron is stored in ferritin, which is a ubiquitously expressed cytosolic iron-storage protein that forms a hetero-oligomeric protein shell composed of ferritin heavy chain (FTH) and ferritin light chain (FTL) [2].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of demonstrations of the bilateral dependence between iron (Fe) metabolism and obesity. It has been shown that serum ferritin concentration is positively correlated with BMI, [10] visceral fat area, subcutaneous fat area, hepatic fat content, and homeostasis model assessment (HOMA), [11] which makes ferritin an indirect marker of insulin resistance. Overweight and obesity are frequent causes of iron deficiency or, inversely, of iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…Se has a wide range of pleiotropic effects including production of active thyroid hormone by incorporating into selenoproteins [34] . Fe acts as essential nutrient utilized in almost every aspect of cell function [35] , and interacts with other trace elements (Cu and Zn) [36] . Adequate dietary supply of Se and Fe is required for a healthy thyroid during development and adolescence [37] .…”
Section: Discussionmentioning
confidence: 99%